A Systematic Literature Review to Identify Successful Elements for Financial Education and Counseling in Groups. Issue 2 (29th January 2018) - Peeters, Nele; Rijk, Kathinka; Soetens, Barbara; Storms, Bérénice; Hermans, Koen
Abstract : This study reviews the literature available on contents, form, and effectiveness of group‐based programs for combined financial education and counseling aimed specifically at populations at risk for financial difficulties. Despite the widespread application of these programs, relatively little is known about their effectiveness. In general, evidence points to positive effects of several programs on knowledge, confidence, and (intended) behavior, but the exact mechanisms through which this is achieved remain unclear. The topics covered differ among studies, but common themes can be identified. It appears of importance to combine education with practical exercises allowing participants to apply the skills they learn. Motivating clients is another important recurring theme. Working in groups provides an added benefit through recognition and peer support. It is important that future research focuses on the mechanisms of change and on long‐term effects, since these remain largely unknown in the current body of literature.